Helminths and helminth communities of Chondrostoma nasus from the Danube River, northwestern Bulgaria - Zaharieva Radoslava G.; Kirin Diana A.; Zaharieva Petya G. (Fisheries & Aquatic Life)
In the 2019–2021 period, a total of 349 specimens of Chondrostoma nasus (L.) from the border zone of the Danube River (Kudelin, Koshava, and Yasen biotopes), in northwestern Bulgaria were subjected to interdisciplinary research. A total of 11 helminth taxa belonging to four classes (Trematoda, Cestoda, Acanthocephala, Nematoda) were identified. Two helminth species (Pomphorhynchus laevis and Contracaecum sp.) were common to common nase from the three biotopes studied. The helminth communities of the species at the level of the component communities and the infracommunities were analyzed for the first time in Bulgaria. Helminth species pathogenic to fishes and humans were found in the helminth communities of Ch. nasus.